Political stability and fiscal policy time series evidence for the Swiss federal level since 1849 - Feld, Lars P.; Schaltegger, Christoph A. (CESifo working papers, 2009)
This paper explores the role of political stability on fiscal policy choices in a time-series analysis over 158 years on the Swiss federal level. We argue that the fiscal-commons problem of public finances is affected by the time-horizon of a finance minister. Arguably, the incentives for an incumbent to maintain a good reputation with sound policy decisions are stronger the longer the time-horizon of a respective term. In addition, a finance minister who succeeds to stay a long time in office normally enjoys a politically powerful position towards the parliament, the administration and the interest groups to influence policy decisions. In contrast, frequent government turnover weakens the position of the finance minister.